Strategy for implementing the application of the regional government information system (SIPD) in the preparation of the regional government work plan (RKPD) documents for West Lampung district - Rudi Agus Hermawan; Andy Cory Wardhani; Agus Susanto (SEAN Institute, 2024)
In line with the increasing development of information technology, requires the development of an organization to take advantage of various technological advances to accelerate the achievement of organizational goals. Regional Government as a public organization must also adapt to advances in information technology starting from the stages of development planning, implementation, and evaluation to reporting. The technique for taking informants uses non-probability sampling. Meanwhile, the data analysis technique uses qualitative analysis, data reduction methods, data presentation, and drawing conclusions or verification. This research uses policy implementation theory in accordance with the opinion of George C. Edward III. The results of this research are 4 strategies for consistentizing the West Lampung Regent's Regulations regarding Changes to Regional Government Work Plans with Scheduling in the SIPD Application, namely: (1) Increasing coordination between Bappeda and BPKD to make changes to the RKPD first, after that carrying out the process of changing the KUA PPAS and APBD, (2) Develop written regulations containing that proposals related to APBD shifts from all OPDs can be made before the schedule for preparing RKPD changes so that the RKPD change process is not disrupted, (3) Improve better coordination between internal Regency Governments and the Central and Provincial Governments regarding possible some regulations require the APBD to be shifted so that the APBD shift process can be carried out more quickly before the RKPD amendment process begins, and (4) Increase the quality of discussions at the APBD stage to avoid errors in the APBD preparation process.